Simulation Based on Trivariate NURBS and Isogeometric Analysis of a Spur Gear - Yusuf, O.T.; Gang, Z.; Wei, W.; Onuh, S.O. (Проблемы прочности, 2015)
The approach provides simulation of the gear design with high-precision profile configuration parameters to accurately predict its load capacity and stress state, which requires incessant efforts, as gear failure modes depend largely on its profile representation. The finite element analysis (FEA) is a well-known effective computational method, which many authors used to estimate the gear tooth strength against the primary failure modes of gears. This method is not only known to be time-consuming but often expensive, it employs approximate geometry that resulted in a coarse mesh.